In the Nick of Time: The Legitimacy of Imposing Deadlines on Appeal and Counter-Appeal Memoranda in Civil Procedure - Cita Yustisia Serfiyani; Angelica Milano Aryani Wibisono; Jeniffer Avrillya Wibisono; Vicko Taniady (Universitas Airlangga, 2026)
The modernization of Indonesia’s civil justice system through the e-Court platform has generated a significant normative conflict by imposing a strict seven-day deadline for submitting appeal and counter-appeal memoranda under Supreme Court Decision Letter No. 363/KMA/SK/XII/2022. This regulation conflicts with several higher legal instruments—including the Herziene Indonesisch Reglement (HIR), RBg, Law No. 20 of 1947, and Constitutional Court Decision No. 22/PUU-XX/2022—which confirm that such submissions are optional and are not subject to fixed time limits. This research offers a comprehensive analysis of the normative inconsistency by employing a legal research method grounded in procedural justice theory. Using statutory and conceptual approaches, it assesses whether the decision letter rests on a valid legal basis and whether it comports with the principles of fair civil procedure. The findings indicate that the decision letter imposes a formal requirement that exceeds the Suipreme Court’s legal authority, creates a conflict of norms, and undermines litigants’ procedural rights. The study therefore recommends that the Supreme Court undertake a judicial review to resolve the inconsistency and restore legal certainty in Indonesia’s civil justice system.